Mechanisms of hepatic tumor promotion by polychlorinated biphenyl mixtures - Dean, Charles E., Jr., author; Benjamin, Stephen, advisor; Baker, Dale, committee member; Tessari, John, committee member; Yang, Raymond, committee member (Colorado State University. Libraries, 2003)
Polychlorinated biphenyls (PCBs) are environmental pollutants that exist as mixtures and are potential humans carcinogens. Despite this, there are relatively few relevant data on interactive biological effects and risk estimation for carcinogenesis remains based on data for individual PCB congeners. Mechanisms by which PCBs exert their promotional carcinogenic effects are unknown. Our studies evaluated the role of alterations of TGFβ signaling pathways in PCB-induced promotion stage of hepatocarcinogenesis. Rats were administered the planar PCB 126 (3,3',4,4',5-pentachlorobiphenyl) and the non-planar PCB 153 (2,2',4,4',5,5'- hexachlorobiphenyl) alone and in combination in a medium term bioassay that included diethylnitrosamine iniation and partial hepatectomy. For PCB 126 and 153, the doses ranged from 0.1-10 and 10-10,000 μg/kg body weight, respectively. Treatment with PCB 126 or 153 alone resulted in a significant (P<0.01) dose dependent increase in preneoplastic foci area and number compared with controls. Treatment with combined PCB 126 and PCB 153 increased preneoplastic focus formation but resulted in a less than additive promotional effect. The antagonistic effect was present at all five PCB 126/PCB 153 dose combinations, including the low doses of PCB 126 and 153 that did not show significant promotional activity alone. An eight-week time course study without the partial hepatectomy was conducted to evaluated alterations in TGFβ signaling, cell proliferation and apoptosis. Treatment with individual and combined PCBs throughout the study did not significantly alter cell proliferation, apoptosis or TGFβ receptor expression compared to initiated and noninitiated controls nor did the formation of altered hepatic foci occur. Immunohistochemistry for alterations in TGFβ, TGFβ II receptor, cell proliferation and apoptosis were evaluated in preneoplastic foci in animals treated with the highest PCB 126 and PCB 153 doses alone and in combination. TGFβ-positive preneoplastic foci increased in PCB 126-treated animals and this correlated with a reduced TGFβ II receptor expression. Treatment with PCB 153 and the PCB mixture did not result in significant changes in receptor expression. Our results show expressions of TGFβ and TGFβ II receptor are significantly altered during the promotion stage of PCB 126-induced hepatocarcinogenesis and suggest that these changes might contribute to the development and progression of preneoplastic lesions.
Keywords: pathology